Glial cells: an important switch for the vascular function of the central nervous system - Gao, Ling; Pan, Xuezhen; Zhang, John H.; Xia, Ying (Frontiers in Cellular Neuroscience, 2023)
In this review, we first describe the current understanding of glial-mediated vascular function affecting the role of the blood-brain barrier (BBB) in central nervous system (CNS) disorders. BBB, mainly composed of glial and endothelial cells (ECs), is the protective structure that orchestrates the transport of substances, including ions, molecules, and cells from brain vessels into or out of the CNS. Then, we display the multiple communication between glial and vascular function based on angiogenesis, vascular wrapping, and blood perfusion in the brain. Glial can support microvascular ECs to form a blood network connecting to neurons. Astrocytes, microglia, and oligodendrocytes are the common types of glial surrounding the brain vessel. Glial-vessel interaction is required for the permeability and integrity of BBB. Glial cells surrounding the cerebral blood vessels can transmit communication signals to ECs and regulate the activity of vascular endothelial growth factor (VEGF) or Wnt-dependent endothelial angiogenesis mechanism. In addition, these glial cells monitor the blood flow in the brain via Ca2+/K+-dependent pathways. Finally, we provide a potential research direction for the glial-vessel axis in CNS disorders. Microglial activation can trigger astrocyte activation, which suggests that microglia-astrocyte interaction may play a key role in monitoring cerebral blood flow. Thus, microglia-astrocyte interaction can be the key point of follow-up studies focusing on the microglia-blood mechanism. More investigations focus on the mechanism of how oligodendrocyte progenitor cells communicate and interact with ECs. The direct role of oligodendrocytes in modulating vascular function needs to be explored in the future.